Rejection of Medical Treatment By Patients In The Perspective of Legal Responsibility - Dhanudibroto, Handojo; Widjaja, Gunawan (Devotion : Journal of Research and Community Service, 2025)
Refusal of medical treatment is an inherent right of every patient based on the principles of autonomy and human rights. In the context of health law in Indonesia, the patient's right to refuse medical procedures is regulated in Law Number 17 of 2023 concerning Health, which gives patients the freedom to accept or refuse medical procedures after obtaining adequate information from medical personnel. However, the legal implications of refusing medical treatment become complex when the decision causes the patient's loss or death, which can trigger potential legal disputes between the patient's family and medical personnel, as well as the hospital. This study uses a normative juridical method with a legal, conceptual, and case approach to analyze the legal responsibility of medical personnel in the context of refusal of patient medical treatment. This paper is intended for the knowledge of health law practitioners and law enforcement, in order to understand the legal consequences of refusing medical treatment by doctors.